2012
DOI: 10.1080/08985626.2012.710260
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cluster connectedness on firm innovation: R&D effort and outcomes in the textile industry

Abstract: Recent research into the clustering effect on firms has moved away from a simplistic view to a more complex approach. More realistic and complex causal relationships are now considered when analyzing these territorial networks. Specifically, this paper attempts to analyze how cluster connectedness moderates the relationship of a firm's innovation effort and the results obtained from this effort. We want to question the commonly accepted direct and positive impact of R&D effort, and moreover, we suggest the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 87 publications
(90 reference statements)
3
22
0
Order By: Relevance
“…Our work is in line with those studies reported in the cluster literature that assumed the network model for these industrial contexts (Branston et al, 2005; Boschma and Ter Wal, 2007; Parrilli and Sacchetti, 2008), more particularly in the Spanish context (Parra-Requena et al, 2010; Molina-Morales and Expósito-Langa, 2012). Within this context we focused on the notion of knowledge brokers, understanding them as actors exchanging different types of knowledge between otherwise unconnected actors in the same location (Graf, 2011; Graf and Kruger, 2011).…”
Section: Conclusion Limitations and Future Researchsupporting
confidence: 91%
See 1 more Smart Citation
“…Our work is in line with those studies reported in the cluster literature that assumed the network model for these industrial contexts (Branston et al, 2005; Boschma and Ter Wal, 2007; Parrilli and Sacchetti, 2008), more particularly in the Spanish context (Parra-Requena et al, 2010; Molina-Morales and Expósito-Langa, 2012). Within this context we focused on the notion of knowledge brokers, understanding them as actors exchanging different types of knowledge between otherwise unconnected actors in the same location (Graf, 2011; Graf and Kruger, 2011).…”
Section: Conclusion Limitations and Future Researchsupporting
confidence: 91%
“…This joint effect increases the firm's knowledge and, consequently, its value creation and innovation. Some examples in this regard are Expósito-Langa et al (2015), Molina-Morales and Expósito-Langa (2012) or Escribano et al (2009). In spite of the above argumentation, some recent body of research remarks that it is also possible to find a partial substitution effect between internal R&D efforts and external information sources such as brokerage activities.…”
Section: Hypothesesmentioning
confidence: 99%
“…Employees in these SMEs have change‐oriented job assignments, as the fashion industry rigorously innovates and brings about changes with intermittent improvements. Products related to fashion and design do not retain their value over a long period of time (Enkel & Gassmann, 2010; Molina‐Morales & Expósito‐Langa, 2012; Singleton, 2013; Zhang, Dong, Ma, Tang, & Cai, 2010). Continuous change is the outcomes of hyper‐competitive markets, technological growth, and globalization (Xerri et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the absorptive capacity can be at some point partially substituted or complemented by external activities, depending on the degree of overlapping. In our opinion, these interactions between internal and external levels of capacities only happen under the cluster conditions, and thus rarely can be applied to different contexts (Molina‐Morales and Expósito‐Langa ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%